Future scenarios of palliative care in health system of Iran: a multi-method study - Barasteh, Salman; Parandeh, Akram; Rassouli, Maryam; Zaboli, Rohallah; Vahedian Azimi, Amir; Khaghanizadeh, Morteza (Frontiers in Public Health, 2024)
Background Paying attention to palliative care has accelerated in Iran in the last 10 years. Considering the trend of aging, increasing burden of chronic diseases and increasing health costs, planning and development of palliative care is necessary in the future. This study was conducted with the aim of explaining the alternative scenarios of palliative care in the health system of Iran until the horizon of 2030. Methods This study was a multi-method scenario planning with a qualitative using multiple methods design, which was conducted in 3 phases in 2018–2020. In the first phase, a list of driving forces was extracted using qualitative interviews and literature review. In the second phase, all factors identified in the previous phase were examined in terms of degree of uncertainty and cross-impact analysis, and two key uncertainties were extracted. In the third phase, based on two key uncertainties, four future scenarios of palliative care were formulated, validated and scenario strategies were presented. Results The results indicate two uncertainties, including “governance of palliative care in the health system” and “acceptance of palliative care by society,” based on which, four scenarios with the names “climbing to the top,” “excruciating climb,” “edge of the abyss” and “The bottom of the valley” were compiled. Conclusion The development of palliative care in health system of Iran is faced with serious uncertainties that it is necessary to focus the developmental activities of palliative care on the two axes of acceptance by society and need for coherent governance by considering all the dimensions and influential components by ministry of health. The application of the results of this research can provide reasonable options for effective interventions and implementation of this category of services to the beneficiaries of palliative care.